Can traffic violations be traced to gender-role, sensation seeking, demographics and driving exposure?. (November 2016) - Oppenheim, Ilit; Oron-Gilad, Tal; Parmet, Yisrael; Shinar, David
Highlights: Traffic violations' self-reports and personal characteristics were collected via a web survey. Violations, as opposed to accidents, could be used as a key measure for traffic safety. Gender role was found to be a better predictor of driver behavior than gender. Abstract: Background: Traffic safety is often expressed as the 'inverse of accidents'. However, it is more than the mere absence of accidents. Past studies often looked for associations between accidents and self-reports like the Driver Behaviour Questionnaire (DBQ; Reason, Manstead, Stradling, Baxter, & Campbell, 1990). The focus in this study changed from counting accidents to quantifying unsafe acts as violations. The objective was to show that drivers' specific violations can be traced to personal characteristics such as sensation seeking (SSS-V; Zuckerman, 1994), gender role (BSRI; Bem sex role inventory, Bem, 1974), demographics, and driving exposure. Method: A web-based questionnaire was distributed, integrating several known questionnaires. Five hundred and twenty-seven questionnaires were completed and analyzed. Results: Sensation seeking, gender role, experience, and age predicted respondents' score on the DBQ, as well as the interaction of sensation seeking with gender and gender role. Gender role was a more valid predictor of driver behavior than gender. Conclusions: The effect of gender role on drivers' self-reported violation tendency is the most interesting and the most intriguing finding of this survey and indicates the need to further examine gender role affects in driving.